Analysis Of The Achievement Of Double Loop Problem Solving (DLPS) Learning Model On Multiple Selection Problems Reviewed From Mathematical Connection Ability Of Vocational School - Agus Riana (IKIP Siliwangi, 2020)
This article presents research related to learning achievement using the double loop problem solving (DLPS) learning model and experimental research methods with a pre experimental design: one-shot case study design using purposive sampling, of class X vocational students in the academic year 2019/2020 on math problems with multiple choice questions. the purpose of this research is to describe the achievement of students' mathematical connection abilities using the double loop problem solving learning model (DLPS), obtain a number of student problems in the process of connecting the form of mathematical problem questions with multiple choice questions. Based on the analysis of the data obtained the results of research at the intended school shows that the percentage of students who have good mathematical connection abilities of students is less than 65%. Thus in the form of multiple choice questions, the double loop problem solving learning model is not achieved in the mathematics learning process